2011
DOI: 10.1021/cg2005024
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth of Clathrate Hydrate in Liquid Water Saturated with a Simulated Natural Gas

Abstract: This paper reports the visual observation of the formation and growth of clathrate hydrate crystals in liquid water presaturated with a simulated natural gas (methane þ ethane þ propane mixture). The compositions of the methane þ ethane þ propane gas mixtures are (i) 90:7:3, (ii) 94.1:5.8:0.1, and (iii) 99.47:0.51:0.02 in molar ratio. A hydrate film first formed to intervene between the mixed gas and liquid water, and then hydrate crystals grew in the liquid water phase. The morphology of hydrate crystals grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 26 publications
6
57
0
Order By: Relevance
“…4). The crystal morphology obtained in this study in the range 7.8 K < T sub < 12.1 K is similar to that of the system with mixed gas (94.1:5.8:0.1) reported by Watanabe et al 21 in the lower subcooling part, i.e. polygonal flat plate crystals.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…4). The crystal morphology obtained in this study in the range 7.8 K < T sub < 12.1 K is similar to that of the system with mixed gas (94.1:5.8:0.1) reported by Watanabe et al 21 in the lower subcooling part, i.e. polygonal flat plate crystals.…”
Section: Resultssupporting
confidence: 88%
“…Hydrate crystal morphology observed in the present study is arranged along the horizontal axis of T sub with mixture gas as reported by Watanabe et al 21 and with methane as reported by Ohmura et al 18 (Fig. 4).…”
Section: Resultssupporting
confidence: 84%
“…Study on the growth mechanism of hydrate crystals is also of great importance for modeling of macroscopic kinetics of hydrate formation with respect to different application fields of gas hydrate. Many theoretical and experimental studies about the hydrate crystal growth have been performed with respect to different subcoolings and compositions of gas mixtures. However, a further understanding of the growth patterns of hydrate crystals is necessary, in view that most of those investigations only examined the formation pattern of hydrate crystals in two dimension.…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that the promoting effect of L ‐leucines may come from their surface activity and surface adsorption (Figure S5, Supporting Information). Visual observations of methane hydrate growth in the quiescent water/methane system disclosed the formation of a rigid hydrate film at the liquid/gas interface, which would hinder further hydrate formation 8. In contrast, L ‐leucine, a typical amphiphilic molecule composed of hydrophilic amine and carboxylic acid groups, along with a hydrophobic aliphatic isobutyl side chain,9 can act as a surfactant to prevent hydrate particles from agglomerating and forming a rigid hydrate film at the liquid/gas interface.…”
mentioning
confidence: 99%
“…That means the guest molecules may affect the formation kinetics of gas hydrates in the presence of promoters such as leucines. It is possible that gas hydrate crystal morphologies are affected by the gas composition,8 or that the same molecule can work as a promoter or an inhibitor depending on the particular conditions of the experiment,14 although a detailed mechanistic study is outside the scope of this first report.…”
mentioning
confidence: 99%